PERLINDUNGAN HUKUM TERHADAP ANAK-ANAK YANG MENJADI KORBAN PENGGUNAAN SENJATA AGENT ORANGE DALAM PERANG VIETNAM - Sandhi Surya, Risa; Palguna, I Dewa Gede; Budi Arsika, I Made (Kertha Negara : Journal Ilmu Hukum; Vol. 03, No. 01, Februari 2015)
This writing aims to discuss the legality of the use of ‘Agent Orange’ weapon during the Vietnam War and the legal protection of children who are victims of the use of such weapon in Vietnam. This paper is a normative legal research that uses statute, case, and historical approaches. It describes and analyzes the chronology of events and legal protection that can be provided to victims of Agent Orange, especially children. This article concluded that the legal protection that can be given to children affected by Agent Orange weapon is not sufficiently provided.
Keywords: Agent Orange, Children, Legal Protection